Pengaruh Persepsi Kualitas Pelayanan Pajak, Sanksi Perpajakan, Biaya Kepatuhan Pajak, Penerapan E-Filing, Pemahaman Perpajakan dan Kepercayaan Terhadap Kepatuhan Wajib Pajak : Studi Empiris pada Kantor Pelayanan Pajak Madya Banjarmasin - Lolita Siregar; Sarwani, Sarwani; Rahma Yuliani (Edunomics Journal, 2025)
This study aims to determine the influence Tax Services Quality, Tax Sanction, Compliance Cost, E-filing, Tax Knowledge, and Tax Payers Trust on taxpayer compliance. The Independent variable is Tax Services Quality, Tax Sanction, Compliance Cost, E-filing, Tax Knowledge, and Tax Payers Trust. While the dependent variable is taxpayer compliance. This research is a quantitative research. The population as the object of research is all Corporate Taxpayers registered and required to report at KPP Madya Banjarmasin. The sample was selected using the purposive sampling method and obtained 145 samples of Corporate taxpayers. The data analysis technique used was multiple regression analysis and analyzed using SPSS 25. The result of this research showed that Tax Services Quality, Tax Sanction, E-filing, Tax Knowledge had an effect on the compliance of Corporate taxpayers registered with KPP Madya Banjarmasin, while the Compliance Cost and Taxpayers Trust had no effect on the compliance of Corporate taxpayers registered with KPP Madya Banjarmasin.